The immediate effects of a dynamic orthosis on gait patterns in children with unilateral spastic cerebral palsy: a kinematic analysis - Martins, Maria Elisabete (2019)
This study analyzes the immediate effects of wearing a Therasuit on sagittal plane lower limb angular displacements during gait in children with unilateral spastic cerebral palsy (US-CP). Seven participants (median age = 7.00 years; ranging from 5.83 to 9.00 years) with US-CP, levels I and II of the Gross Motor Function Classification System, were assessed with kinematic gait analysis in three different conditions: (A) Baseline; (B) Therasuit without elastics and (C) Therasuit with elastics. Significant improvements were observed at the hip joint of both lower limbs during most of the gait cycle in participants wearing a Therasuit, including a decrease in the flexion pattern at the initial contact and swing phase in both lower limbs, and an increase in the extension pattern in the paretic lower limb during the stance phase. At the knee joint in the paretic lower limb, significant differences were found between the baseline and Therasuit with elastics conditions on the knee angle at initial contact, and between baseline and both Therasuit conditions on the flexion angle at swing phase. However, the inter-individual variability in kinematic patterns at the knee joint was high. At the ankle joint, decreased plantar flexion at initial contact and increased dorsiflexion during stance and swing phases were observed at the Therasuit with elastics condition, helping to correct the equinus-foot in the paretic lower limb during the whole gait cycle. The Z-values showed large effect sizes particularly for most of the angular hip variables in both lower limbs and for the angular ankle variables in the paretic lower limb. The Therasuit seems to have some positive immediate effects on gait kinematics in children with spastic unilateral cerebral palsy by providing a more functional and safer gait pattern. Future investigations with larger samples are recommended to further support these findings.